2017
DOI: 10.15666/aeer/1501_225244
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of the Huseedwild – A Seed Weight and Germination Database of the Pannonian Flora – Through Analysing Life Forms and Social Behaviour Types

Abstract: Abstract. In this paper, we present the HUSEED wild , which is an online seed weight and germination database relying on our investigations concerning the regional seed collection (Pannon Seed Bank) of the Pannonian flora (available at: http://huseed.nodik.hu:8243/en/wild). Our data of 806 taxa (sensu species and subspecies) represent nearly 40% of the Pannonian flora. With our database, we contribute to former Hungarian databases with seed weight data of 50 taxa, and data of 20 taxa are first to be published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
3
13
0
1
Order By: Relevance
“…A short description of functional traits used in the analysis is given in Table . Data were obtained from local or Central European databases (LEDA—Kleyer et al ; HUSEED—Peti et al ) and literature sources (Csontos ; Halassy ; Király ; Lhotsky et al ). Where multiple trait data were available, the order of preference was local, national, and then regional data.…”
Section: Methodsmentioning
confidence: 99%
“…A short description of functional traits used in the analysis is given in Table . Data were obtained from local or Central European databases (LEDA—Kleyer et al ; HUSEED—Peti et al ) and literature sources (Csontos ; Halassy ; Király ; Lhotsky et al ). Where multiple trait data were available, the order of preference was local, national, and then regional data.…”
Section: Methodsmentioning
confidence: 99%
“…Baskin and Baskin (1998) also provided information on inducing germination and increasing germination rates for some species, and highlighted that several factors, such as temperature, moisture or salinity have to be tested to identify the most appropriate conditions (Covell et al 1986, Gulzar and Khan 2001, Huang et al 2003, Roberts 1988. To maximise germination rates, the most suitable germination method has to be identified (Peti et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Germination capacity has mostly been studied for agricultural crops, as well as garden and ornamental plants (ISTA). In spite of the increasing involvement of seed traits in ecological research (Hintze et al 2013, Kelemen et al 2015, Török et al 2013, we only found two databases, which contained information about the seed germination capacity of the wild plant species of the Central European flora (SID -RBGK 2018, HUSEED wild - Peti et al 2017). The large international plant trait databases lack such information (LEDA - Kleyer et al 2008, D 3 -Hintze et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The germination percentage of about 55 was achieved, which is an acceptable value, considering the long storage period of the seeds. Seed germination is one of the di cult-to measure plant reproductive traits, but it is a trait often used in research (Peti et al 2017). In the short-lived plant species Ensslin et al (2017) found that seed dormancy could be highly variable.…”
Section: Discussionmentioning
confidence: 99%